Comparative advantage of improved feed trough and the traditional feeding material for efficient utilization of crop residue at small-scale farmers in Northwestern Tigray, Ethiopia - Teklemariam Abadi; Kibrom Gebremedhin; Desale Gebretsadik; Daniel Desta (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2023)
The study was conducted to reduce the high feed wastage by practicing the improved feed trough in the study area. The trail was conducted at Tahtay Koraro district Northwestern zone of Tigray, Ethiopia. Improved feed trough was constructed on a total of 20 interested farmers. Both quantitative and qualitative data were collected andanalyzed using descriptive statistics. The result showed that the improved feed troughs reduced feed waste significantly in the study area. That is 4.13% and 25% feed loss respectively in improved and traditional feed troughs. The result from the farmers perception also shows that, the farmers were preferred the technology in its less feed wastage, reduces feed contamination, gives an opportunity for persons to do other task than keeping animals, comfortable for the animals, reduces feed competition among the animals; and protects the feed from rain and sun. But farmers are less preferred the technology in its cost for its construction. Therefore, based on the result it is recommended that the technology has to be popularized and promoted to the large number of the farmers of the area for the efficient crop residue utilization.